2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2463
|View full text |Cite
|
Sign up to set email alerts
|

Physical composition of carcass, commercial cuts and meat characteristics of young bulls fed millet-based diets containing increased crude glycerin levels

Abstract: Assessment of carcass and meat characteristics of Nellore young bulls finished in feedlot with crude glycerin levels (0, 60, 120, and 240 g kg -1 dry matter) in millet-based diets. Twenty-eight young bulls with mean age of 18 months and average weight of 357 ± 23.56 kg were used. The animals were distributed in a completely randomized design with four treatments and seven replicates. It was observed that the physical composition and edible portion of the carcass were not affected by crude glycerin levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(51 reference statements)
2
1
1
Order By: Relevance
“…The results of this study disagree with those presented by Moreira et al (2016b), who found that among the carcass primal cuts, only the forequarter weight (kg and % of the cold carcass weight) varied with the inclusion of crude glycerin (0, 6, 12, and 24%) in pearl millet grain-based diets, and that it increased linearly, associated with an increase in average daily gain and manifestation of sexual dimorphism. The results of this current study are instead more similar to those obtained by Van Cleef et al (2014), who did not find an alteration of the commercial primal cuts of the carcass of young Nellore bulls consuming levels of crude glycerin (0%, 7.5%, 15%, 22.5%, and 30% of dry matter) in corn-based diets, a finding that can be explained by the lack of variation in average daily gain.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study disagree with those presented by Moreira et al (2016b), who found that among the carcass primal cuts, only the forequarter weight (kg and % of the cold carcass weight) varied with the inclusion of crude glycerin (0, 6, 12, and 24%) in pearl millet grain-based diets, and that it increased linearly, associated with an increase in average daily gain and manifestation of sexual dimorphism. The results of this current study are instead more similar to those obtained by Van Cleef et al (2014), who did not find an alteration of the commercial primal cuts of the carcass of young Nellore bulls consuming levels of crude glycerin (0%, 7.5%, 15%, 22.5%, and 30% of dry matter) in corn-based diets, a finding that can be explained by the lack of variation in average daily gain.…”
Section: Resultscontrasting
confidence: 99%
“…In this study, the meat texture, marbling, shear force of the muscle fibers, loss of liquid from thawing and cooking, and total loss were not influenced (P > 0.05) by the levels of crude glycerin in the diets (Table 4). These results are similar to those obtained by Moreira et al (2016b), who evaluated similar crude glycerin levels to those of the present study in millet grainbased diets and did not find significant alterations in these meat parameters. Similarly, Leão et al (2013) did not find alterations in texture, tenderness, marbling, liquid losses from thawing and cooking, or total liquid losses in meat from steers or cull cows fed increasing levels of crude glycerin in corn grain-based diets.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations